TINGKAT PRODUKTIVITAS DAN PEMASARAN UBI KAYU DI JORONG PILADANG KECAMATAN AKABILURU KABUPATEN 50 KOTA - Randa Permata Ilahi; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims 1) to determine the productivity level of cassava plants in Jorong Piladang, Akabiluru District, 50 Kota District, 2) Knowing the cassava marketing system in Jorong Piladang, Akabiluru District, 50 Kota District.This research method is qualitative and the location of the research is carried out in Jorong Piladang, Akabiluru District, Lima Puluh Kota Regency. Techniques to determine informants using purposive sampling and observation data techniques in research using participatory techniques, interviews, and documentation. Technique of data analysis by means of data reduction, data presentation, and data retrieval as well as data validity techniques using time extension and increasing persistence. The results of this study were: 1) The productivity level of Cassava in Jorong Piladang, Akabiluru District, Lima Puluh Kota Regency on average increases every year. The productivity of this cassava can increase because it depends on the quality of the cassava, good weather, then it can be built by agricultural land owned by cassava farmers and sufficient capital. 2) The Marketing System for Cassava in Jorong Piladang, Akabiluru Subdistrict, Fifty Cities District, is carried out by selling raw and processed cassava to nearby markets and outside the region.